Implementasi Of Complete Systematic Land Registration System Model Policy in Bone Regency - Siraj, Muhammad Luthfi; Aslinda, Aslinda; Zainal, Henni; Syarifuddin, Syarifuddin (Universitas Negeri Makassar, 2023)
This research aims to determine the implementation of the Complete Systematic Land Registration Program (PTSL) in the Context of Accelerating Land Registration at the Bone Regency Land Office as well as supporting and inhibiting factors for the implementation of the Complete Systematic Land Registration Program (PTSL) at the Makassar City Land Office. This research uses a qualitative approach with descriptive methods. Data collection was carried out through observation, interviews and documentation techniques. The data analysis technique used in this research is interactive data analysis through the stages of data condensation, data presentation, and drawing conclusions. The results of this research indicate that the implementation of the Complete Systematic Land Registration Program (PTSL) system model at the Bone Regency Land Office is considered not to be implemented effectively, although there are still several shortcomings in its implementation. This can be seen from the policy standards and objectives, the characteristics of implementing agencies/agencies, communication between organizations, the attitude of implementers in implementing PTSL which has gone well, but there are still deficiencies in policy resources and the economic, social and political environment.